Assignment of the major histocompatibility complex to a region of the short arm of human chromosome 6. - Francke, U (1977)
Interspecific cell hybrids containing defined parts of human chromosome 6 were used for regional mapping of gene loci previously assigned to chromosome 6: the human leukocyte antigens (HLA) region, phosphoglucomutase-3 (PGM3; alpha-D-glucose-1,6-bisphosphate:alpha-D-glucose-1-phosphate phosphotransferase, EC 2.7.5.1) and malic enzyme-1 [malic dehydrogenase(decarboxylating) (NADP+), L-malate:NADP+ oxidoreductase (oxaloacetate-decarboxylating), EC 1.1.1.40]. Human fibroblasts containing a balanced reciprocal translocation between the short arms of chromosome 1 and chromosome 6--designated t(1;6) (p3200;p2100)--were fused with an established line of Chinese hamster cells. Hybrid clones with segregating human chromosomes were studied for the presence of the translocation chromosomes 1T and 6T and their normal homologues 1 and 6. Six clones that had retained 1T, three clones with 6T, and three clones with 6 and 6T as controls, were analyzed by a microabsorption test for expression of the allelic antigens HLA-A2 and HLA-A3, both of which were present on the human parental cells. HLA-A2 segregated with the 1T translocation chromosome and HLA-A3 with the normal chromosome 6. Hybrid clones with 6T did not possess an HLA-A gene. In contrast, human PGM3 and malic enzyme-1 expression segregated with the 6T translocation chromosome. These results indicate the location of the major histocompatibility complex in region 6p2100 leads to 6pter of the short arm of chromosome 6. The genes for PGM2 and malic enzyme-1 map in region 6p2100 leads to 6qter. The HLA:PGM3 genetic map distance is 15 centimorgans in males, as established by family studies. This allows rather precise mapping of both loci because HLA is distal and PGM3 proximal to the translocation breakpoint in band 6p2100. The findings are consistent with earlier conclusions that HLA is proximal to 6p22. Quantitative correlation between the density of HLA antigens on the hybrid cell surface and the number of copies of the respective HLA gene-bearing chromosome suggests a gene dose effect for cell surface molecules, as it exists for intracellular gene products.